Green metal nanotechnology in monogastric animal health: current trends and future prospects — A review - Chin, Sungyeon; Moniruzzaman, Mohammad; Smirnova, Elena; Thoung, Do Thi Cat; Sureshbabu, Anjana; Karthikeyan, Adhimoolam; Lee, Dong I.; Min, Taesun (Animal Bioscience, 2025)
Green nanotechnology is an emerging field of research in recent decades with rapidly growing interest. This integrates green chemistry with green engineering to avoid using toxic chemicals in the synthesis of organic nanomaterials. Green nanotechnology would create a huge potential for the use of nanoparticles for more sustainable utilization in improving animal health. Nanoparticles can be synthesised by physical, chemical and biological processes. Traditional methods for physical and chemical synthesis of nanoparticles are toxic to humans, animals and environmental health, which limits their usefulness. Green synthesis of nanoparticles via biological processes and their application in animal health could maximize the benefits of nanotechnology in terms of enhancing food animal health and production as well as minimize the undesirable impacts on Planetary Health. Recent advances in nanotechnology have meant different nanomaterials, especially those from metal sources, are now available for use in nanomedicine. Metal nanoparticles are one of the most widely researched in green nanotechnology, and the number of articles on this subject in food animal production is growing. Therefore, research on metal nanoparticles using green technologies have utmost importance. In this review, we report the recent advancement of green synthesized metal nanoparticles in terms of their utilization in monogastric animal health, elucidate the research gap in this field and provide recommendations for future prospects.